Ocular Symptoms in Pre- and Perimenopausal Woman Infected with Demodex spp. - Danuta Kosik-Bogacka; Natalia Łanocha-Arendarczyk; Renata Pilarczyk; Daria Schneider-Matyka; Karolina Kot; Konrad Grzeszczak; Joanna Pyzia; Elżbieta Grochans (Pathogens)
The aim of this study was to determine the subjective ocular symptoms in pre- and perimenopausal women infected with Demodex folliculorum and D. brevis. Eyelashes were taken from pre- and perimenopausal women aged from 45 to 69 years (n = 253) and younger women aged from 3 to 40 (n = 204) from the West Pomeranian Voivodeship located in Poland. The prevalence of mites was analyzed according to age and subjective ocular symptoms. Demodex spp. were detected in 75/253 (29.64%) of pre- and perimenopausal women and in 25/204 (12.25%) of younger women. Demodex folliculorum or D. brevis was observed in 72/252 (28.45%) and 1/253 (0.4%) of pre- and perimenopausal women, respectively, but the coinfection of D. folliculorum and D. brevis was noted in 2/253 (0.79%) of women. In young women, only D. folliculorum was detected. Single Demodex spp., multiple parasites, and numerous mites were reported in about 75%, 17%, and 8% of the examined women, respectively. There was a statistically significant relationship between Demodex spp. infestation and the occurrence of dryness of the eyes. Changes occurring in the female body during the pre- and perimenopausal periods lead to an increased incidence of Demodex spp. infestation. Women who report dryness of the eyes should have their eyelashes microscopically examined for Demodex spp.